(untitled) (Research, Society and Development, 2019)
The diversity of the employment of steel corroborates its great importance to society. Due to its versatility and wide field of operation, steel can be used submerged in the ground in the construction of extensive pipelines, pipelines and tanks to transport fuel. The constant contact between the steel pipe and the soil, over time, renders it exposed to corrosive action. As a result, high direct costs are involved with inspection, maintenance and replacement of parts, and indirect costs due to health problems resulting in contamination, depletion of mineral resources, perforations with loss of materials, besides environmental damages. The study of corrosive processes has grown greatly and the knowledge of both the principles of corrosion and corrosion protection is essential in the search for solutions to mitigate the effects of corrosion, to prevent their occurrence and develop materials with a better resistance. API 5L X70 steels are used in pipelines that transports gas, oil and its derivatives where high mechanical and corrosion resistance are required. In this way, these steels are susceptible to the corrosive process, since they are in direct contact with diverse Brazilian soils and environments. In the present work, the behavior of API 5L X70 steel with and without niobium coating was evaluated in soil chemically treated with acid solutions (simulating acid rain) and basic (simulating soil liming). Techniques such as thermal spraying (for sample coating), experimental corrosion tests and scanning electron microscopy were used in order to identify the corrosion products. At the end, the forms and types of corrosion obtained in the test specimens were classified, the corrosion rate was calculated and the efficiency and the technical feasibility of the niobium coating were evaluated in addition to their anticorrosive properties.